DUE TO THE LAW OVERVIEWING THE PACT PRINCIPLE SUNT SERVANDA TOWARDS THE SETTLEMENT OF BANKRUPTCY DISPUTES IN LAW NUMBER 37 OF 2004 CONCERNING BANKRUPTCY AND OBLIGATIONS OF DEBT PAYMENT - Devid Feizar Montana (Awang Long Law Review, 2021)
The settlement offered by the debtor to the creditor is basically to settle debt disputes and claims out of court. As it is known that in the case of bankruptcy, namely the existence of a process of implementing the provisions of Article 1131 and Article 1132 of the Civil Code, which aims to divide the assets of the debtor fairly, it is intended that creditors obtain prior implementation (pari passu) than others, as well as creditors obtain greater repayments. to others (prostata). However, the provisions of Article 303 of the UUK and PKPU of course raise problems regarding the legal force of the principle of the sunt servanda agreement in the form of an arbitration clause that is relevant for bankruptcy disputes, so as a result of the law violation of the principle of Pacta sunt servanda in bankruptcy disputes. These problems cause legal uncertainty to realize legal certainty as a fundamental value in law. Therefore, in this case, the DPR should immediately review and then revise the UUK and PKPU which are oriented towards prioritizing the Pacta sunt servanda principle in contract law, including business agreements and resulting in bankruptcy. And judges who are expected to better understand the ins and outs of bankruptcy.